Reconstruction of the Concept of Integrative Happiness: A Comparative Study Between Al-Farabi Philosophy of Virtue and Martin Seligman's Positive Psychology - Ahmad Nadif Muhlisin; Achmad Khudori Soleh; Abdul Hakim (Prodi Tasawuf dan Psikoterapi Fakultas Usluhuddin dan Dakwah, Universitas Islam Negeri (UIN) Syekh Wasil Kediri, 2026)
Happiness is the most universal goal of human life. Al-Farabi defines happiness as the highest purpose of life. Meanwhile, according to Seligman, happiness is based on positive psychology, which emphasizes the importance of well-being as the primary goal of human beings. This study aims to identify the differences between the concepts of happiness proposed by these two scholars and the ways to achieve happiness according to each of them. The research employs a qualitative approach using a literature review method. The analysis was conducted by examining scholarly journal articles published online until scientifically sound conclusions were reached. The findings show that: (1) According to Al-Farabi, happiness is the highest goal of human life, pursued for its own sake through the harmony of reason, the soul, and behavior, with its sources rooted in the perfection of reason, knowledge, social relationships, and spiritual connection. It is attained through sincere intention, virtuous deeds, mastery of the four virtues, and moderation, while distinguishing between false happiness and true happiness. (2) Seligman views happiness as psychological well-being measured through positive emotions and meaningful activities, as formulated in the PERMA model. Its sources include positive experiences, flow, healthy relationships, meaning in life, and personal achievement. It can be achieved through the pleasant life, the good life, and the meaningful life. The forms of happiness include emotional happiness, meaning in life, personal development, and the state of flourishing. (3) Both scholars share the view that meaning in life is a key element in achieving happiness.